Modeling and design of an adaptive control for VSC-HVDC system under parameters uncertainties - Mohamed amine Kazi; Radouane Majdoul; Nadia Machkour (Institute of Advanced Engineering and Science, 2021)
The growing demand for electricity and the increasing integration of clean energies into the electrical grids requires the multiplication and reinforcement of high-voltage direct current (HVDC) projects throughout the world and demonstrates the interest in this electricity transmission technology. The transmitting system of the voltage source converter-high-voltage direct current (VSC-HVDC) consists primarily of two converter stations that are connected by a dc cable. In this paper, a nonlinear control based on the backstepping approach is proposed to improve the dynamic performance of a VSC-HVDC transmission system, these transport systems are characterized by different complexities such as parametric uncertainties, coupled state variables, neglected dynamics, presents a very interesting research topic. Our contribution through adaptive control based on the backstepping approach allows regulating the direct current (DC) bus voltage and the active and reactive powers of the converter stations. Finally, the validity of the proposed control has been verified under various operating conditions by simulation in the MATLAB/Simulink environment.